2005
DOI: 10.1038/nn1522
|View full text |Cite
|
Sign up to set email alerts
|

Nonsynaptic GABA signaling in postnatal subventricular zone controls proliferation of GFAP-expressing progenitors

Abstract: In the postnatal subventricular zone (SVZ) local cues or signaling molecules released from neuroblasts limit the proliferation of glial fibrillary acidic protein (GFAP)-expressing progenitors thought to be stem cells. However, signals between SVZ cells have not been identified. We show that depolarizations of neuroblasts induce nonsynaptic SNARE-independent GABA A receptor currents in GFAP-expressing cells whose time-course depends on GABA uptake in acute mouse slices. We found that GABA A receptors are tonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
450
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(479 citation statements)
references
References 45 publications
21
450
3
Order By: Relevance
“…Previous work demonstrated that GABA is involved in the control of OB neurogenesis by regulating proliferation and migration of neuronal precursors in the rostral migratory stream (Bolteus and Bordey, 2004;Liu et al, 2005). Our findings extend the role of GABA to the control of dendritic initiation.…”
Section: Discussionsupporting
confidence: 82%
“…Previous work demonstrated that GABA is involved in the control of OB neurogenesis by regulating proliferation and migration of neuronal precursors in the rostral migratory stream (Bolteus and Bordey, 2004;Liu et al, 2005). Our findings extend the role of GABA to the control of dendritic initiation.…”
Section: Discussionsupporting
confidence: 82%
“…This suggests that distinct precursor cell populations respond to glutamate/GABA in different ways. In adult SVZa, glutamate and GABA have been reported to exert opposing effects on progenitor cells: glutamate activates (Brazel et al, 2005) while GABA inhibits (Liu et al, 2005) their proliferation. There- fore, it is possible to speculate that these two endogenous amino acids may differentially affect neural or neuronal progenitors in monkey SVZa to achieve precursor cell proliferation/differentiation with either retention in SVZa or migration toward the olfactory bulb.…”
Section: Discussionmentioning
confidence: 99%
“…However, the opposite effect has been reported for secondary progenitors located in the embryonic subventricular zone [3], where GABA A R activation reduces DNA synthesis/mitosis possibly via depolarization-mediated Ca 2þ entry [4]. GABA signaling exerts a complex regulation also in the adult subependymal zone (SEZ) where neuroblasts and glial fibrillary acidic protein (GFAP)-expressing cells, which include stem cells as well as astrocytes, regulate ambient GABA levels, by mediating its nonsynaptic release and uptake, respectively [5]. In turn, GABA A R activation downregulates neuroblast proliferation and migration [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…In turn, GABA A R activation downregulates neuroblast proliferation and migration [6][7][8]. Activation of GABA A R also inhibits the proliferation of GFAP-expressing cells in the adult niche [5]. However, the cellular mechanisms underlying these effects are still unclear.…”
Section: Introductionmentioning
confidence: 99%